The Learning Strategies of Islamic Religious Education Teachers in Developing Students' Ability to Express Opinions in Grade VIII at SMP Muhammadiyah 07 Medan - Husni Ayustia (Yayasan Rahmat Islamiyah, 2024)
This research aims to develop students' ability to express opinions in Islamic Religious Education classes. The approach used is qualitative descriptive with interview, observation, and documentation methods to identify students' challenges and needs in learning. Based on the results of the analysis of case studies, it was found that the use of interactive learning methods, such as group discussions, student presentations, question and answer methods, as well as contextual approaches that are relevant to students' daily lives, can significantly improve students' ability to express opinions. This innovation also encourages more cognitive and reflective learning, so that students can understand the importance of being good at expressing opinions. Thus, innovative learning methods are expected to be able to create students who are skilled and confident in expressing their opinions.